If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = -8x + 6x Combine like terms: -8x + 6x = -2x 18 = -2x Solving 18 = -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 18 + 2x = -2x + 2x Combine like terms: -2x + 2x = 0 18 + 2x = 0 Add '-18' to each side of the equation. 18 + -18 + 2x = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 2x = 0 + -18 2x = 0 + -18 Combine like terms: 0 + -18 = -18 2x = -18 Divide each side by '2'. x = -9 Simplifying x = -9
| 7+6x+6x=47 | | 4x^2-16x-33=0 | | 5/6x-7/8=1/6x-1/4 | | 3/2x-(3-4x)=1/3 | | 3(3)+2(5)=60x-500 | | 5+14a=9x-5 | | 2/3×-11=14 | | -.12x^2+2.4x=8 | | y=7sinx-4 | | (x-1/3x)^2 | | 2x^3+6x^2=1 | | x=2(x+29) | | -54x=10 | | x=2x+58 | | 17x-6=10x-13 | | p=2x+58 | | 48*38= | | x=6+9 | | 7x-2-2x+5=-2x+1+6x | | 1.52=3.16(y-8.62) | | 1.52=(y-8.62) | | ydx=(3x-y^3)dy | | 6n+9=-3n-27 | | y=0.25(x-5)(x-1) | | (x)(x)+3x+2= | | ydx-(3x-y^3)dy=0 | | 2.3x+14= | | n/3=5n-42 | | (p/2)/2 | | 3+3=8x+23 | | (x)(x)-11x+18=0 | | 3/2y-8=-5 |